Domain optimization problem for stationary heat equation - Henrot, Antoine; Horn, Werner; Sokołowski, Jan (Zielona Góra: Uniwersytet Zielonogórski)
In the paper, the support of a Radon measure is selected in an optimal way. The solution of the second-order elliptic equation depends on the measure via the mixed-type boundary conditions. The existence of a solution for a class of domain optimization problems is shown. A relaxed formulation of the optimization problems is proposed. The first-order necessary optimality conditions are derived.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka